2015
DOI: 10.1002/2015wr017446
|View full text |Cite
|
Sign up to set email alerts
|

Large wood transport and jam formation in a series of flume experiments

Abstract: Large wood has historically been removed from streams, resulting in the depletion of instream wood in waterways worldwide. As wood increases morphological and hydraulic complexity, the addition of large wood is commonly employed as a means to rehabilitate in-stream habitat. At present, however, the scientific understanding of wood mobilization and transport is incomplete. This paper presents results from a series of four flume experiments in which wood was added to a reach to investigate the piece and reach ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…It is probable that some, if not all, transported in‐stream wood will be trapped and deposited within the catchment (e.g. Braudrick et al , ; Gurnell et al , ; Bocchiola et al , ; Dixon and Sear, ), as stable large wood and logjams have been shown to be effective trapping locations for mobile wood in the channel (Davidson et al , ), furthermore, it is probable that some longer pieces less than 30 cm in diameter would also remain stable. Although these values will be an underestimate of total in‐stream dead wood biomass it is a useful measure of the likely relative abundance of logjam features in small and medium‐sized forest streams (Gurnell et al , ), furthermore total and average in‐stream wood volumes have been shown to be heavily dependent on the largest pieces of wood (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…It is probable that some, if not all, transported in‐stream wood will be trapped and deposited within the catchment (e.g. Braudrick et al , ; Gurnell et al , ; Bocchiola et al , ; Dixon and Sear, ), as stable large wood and logjams have been shown to be effective trapping locations for mobile wood in the channel (Davidson et al , ), furthermore, it is probable that some longer pieces less than 30 cm in diameter would also remain stable. Although these values will be an underestimate of total in‐stream dead wood biomass it is a useful measure of the likely relative abundance of logjam features in small and medium‐sized forest streams (Gurnell et al , ), furthermore total and average in‐stream wood volumes have been shown to be heavily dependent on the largest pieces of wood (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The modelling of the clogging process has to be improved in the future. Recently, some experiments showed possible ways to improve the modelling of this process [99][100][101][102]. For this question, we recommend using more detailed and fully coupled models, i.e., those in [60].…”
Section: Discussionmentioning
confidence: 99%
“…The interlacing or wedging of key pieces into standing live trees on the floodplain provides a way to increase the longevity of the jam without the need for the steel cables, bolts, and imported boulders used in standard practice. A growing body of research (Merten et al 2010;Davidson et al 2015;Wohl, in press) supports the importance of these factors in jam stability.…”
Section: Discussionmentioning
confidence: 99%
“…However, the composition and volume of jam material controls stream velocities and shear stress in and around the jam (Manners et al 2007). Piece irregularities, especially rootwads, play a large role in determining piece stability as shown in flume experiments (Davidson et al 2015) and natural settings (Merten et al 2010).…”
mentioning
confidence: 99%